Estudo histomorfométrico da aorta torácica da ninhada de ratas submetidas á desnutrição no período de lactação - Carvalho, Ronaldo Miguel [UNIFESP] (2019)
Objective: To evaluate the effects and morpho-quantitative changes of the hypoprotein diet during maternal lactation in the thoracic aorta of offspring. Methods: Female wistar rats were mated with male of the same species at four months of age. Until the birth of the offspring, all the animals received commercial ration. After the birth of the offspring, the puerperae were divided into two groups, a control group that continued the diet with commercial ration and the restricted group that received ration with the same caloric amount, but with a protein content 8% lower than the control group ration .The weight of both offspring and lactating was obtained throughout the lactation period. After weaning at 21 days of age, these animals were euthanized and the thoracic aorta was removed and processed histologically. After the paraffin processing and inclusion of the aorta of the offspring, the sections were made in microtome and stained with hematoxylin - eosin and resorcin - fuchsin from Weigert for histological analysis of the elastic fibers. Results: The offspring of both groups were born with similar body mass. During the 21 days of breastfeeding, offspring fed by malnourished mothers did not gain weight as did the control mothers group.The restricted group obtained only 39% of the body mass of the control group. The matrices of the hypoproteic group lost weight over the diet in relation to the weight on day 0. Histological analysis of the aorta in the restricted group showed a higher fiber compaction and a lower amount of extracellular matrix in relation to the control.This apparent compaction and lower material deposition were observed with the histomorphometric analysis, where the restricted experimental group obtained the mean layer thickness significantly lower than the control group. Conclusion: The hypoprotein diet of puerperal women during the breastfeeding period influences the offspring's weight gain and the thickness of the aortic mid-layer, even though diet during pregnancy were balanced.